Analyzing Students’ Opinions about their Learning Environments and Study Approaches with Bayesian Modeling - Kuikka, Liisa; Salokekkilä, Pirkko; Repo, Saara; Ryynänen, Olli-Pekka (International Journal of Psychotherapy Practice and Research, 2017)
Our own long term experiences as clinical teachers among undergraduate medical students have generated the interest to investigate the plausible connection between students’ study orientation and their learning experiences in small groups.The objective of the study was to assess the hypothesis whether learning in small groups may contribute to study motivation. Participants were 52 undergraduate medical students (10-12 in each group) in the primary health care course between 1st and 5th year during the spring term 2012. The questionnaires used were the Inventory of General studies (IGSO) for study orientation and IQ questionnaire for group learning. The data were analyzed by Bayesian network modeling. In this study, the application used was the Bayminer (www.BayMiner.com) non-linear visualization modeling software. Positive atmosphere in a small group increases study motivation and commitment and predicts mutual trust and gives space to new ideas, where contradictive views can raise interesting discussions. Based on Bayesian modeling it seems that the experience of motivational problems in the present studies may be an indicator of study alienation and connected with the perception of small group dysfunctionality.
Keywords: Bayesian modeling; learning enviroment; study approaches